Self-assessment management system in local government units. Comparison of „Institutional Development Planning (PRI)” and „The Common Assessment Framework (CAF)” - Żabiński, Michał (Journal of Public Governance, 2013)
The paper is a comparison of the two most popular methods of self-esteem in Poland the quality management system used by local government units (“Common Assessment Framework CAF 2006” – CAF model, “Institutional Development Planning” – a method PRI). The introduction to the article is devoted to the origins of the phenomenon of improving the quality of administration and management in the history of both these methods. Later in this article was made comparative analysis of both these methods against criteria such as: self-construction process, the structure of the criteria for self-assessment, the costs of implementing this method in the time required to carry out self-assessment, the impact on the organization, factors affecting the possibility of implementing the chosen method of JST. Article Summary of conclusion about the possibility of using the methods by local government units. This section contains information to facilitate informed choices representatives of local government units to implement the method. This information is presented in a synthetic manner. Both methods were compared in this section in terms of social, economic, organizational and technical two different methods.